Diagnostic utility of endobronchial ultrasound (EBUS) features in differentiating malignant and benign lymph nodes - A systematic review and meta-analysis. (September 2020) - Agrawal, Sumita; Goel, Akhil Dhanesh; Gupta, Nitesh; Lohiya, Ayush; Gonuguntla, Hari Kishan
Abstract: Background: EBUS is being widely used today for echolocation of lymph nodes for FNAC. We present a systematic review and meta-analysis to assess the diagnostic accuracy of EBUS characteristics of lymph nodes in diagnosing malignancy. Methods: A systematic search of published literature was undertaken using databases like PubMed, Web of Science, Cochrane, Google Scholar and Researchgate. Those studies reporting any endobronchial ultrasonography features of malignant lymph nodes like size, margins, echogenicity, shape, central hilar structure (CHS), coagulation necrosis sign (CNS) or color power doppler index (CPDI) were included for review. Random effects model was used to calculate pooled sensitivity, specificity, positive and negative likelihood ratios (LR), and diagnostic odds ratio (DOR). The review protocol was registered with the International prospective register of systematic reviews (PROSPERO registration no. CRD42019117716). Results: 992 articles were retrieved of which 542 articles were evaluated in detail and finally 29 articles met the inclusion criteria. All EBUS features except CPDI showed a statistically significant area under the SROC curve. CNS showed highest area under the SROC curve [0.81 (SE: 0.09)] with maximum pooled specificity [0.93, 95%CI: 0.92–0.94], maximum pooled LR+ [5.12, 95%CI: 2.56–10.2] and DOR [9.23, 95%CI 3.85–22.15]. Maximum sensitivity was seen for CHS 0.91 [95%CI: 0.90–0.92]. Conclusion: EBUS features have the potential to help in more precise location of a malignant lymph node thereby helping in increasing the diagnostic yield. However, high diagnostic accuracy of various EBUS features can currently only be said to supplement tissue diagnosis. Highlights: CNS is the most specific and absence of CHS is the most sensitive of all EBUS features for malignant lymph nodes. Size alone may not be a very accurate parameter in ascertaining malignant status of a lymph node. A combination of various features when used together may have better diagnostic utility. However more prospective studies are needed to ascertain this conclusively. EBUS features can only be used as a guiding factor while doing the lymph node sampling and may not replace tissue sampling.